GCT-21. Long-term outcome and follow up of intracranial germ cell tumors: Reduced-dose radiotherapy and intensified chemotherapy improves clinical outcome and quality of life for long-term survivors. (3rd June 2022) - Kagawa, Naoki; Miyamura, Takako; Yamasaki, Kai; Hirayama, Ryuichi; Kijima, Noriyuki; Okita, Yoshiko; Nakagawa, Tomoyoshi; Hara, Junichi; Kishima, Haruhiko
Abstract: BACKGROUND: Intracranial germ cell tumors (iGCT) are heterogeneous tumors with several histopathology. Chemoradiotherapy is effective and required for treatment against them, but optimal treatment intensity should be selected from the viewpoint of both improvement of clinical outcome and avoidance of late complications. We introduced a protocol with reduced-dose radiotherapy and intensified chemotherapy for iGCT. OBJECTIVE: We retrospectively analysed the clinical outcome, especially for non-germinomatous germ cell tumors and long-term clinical outcome of late complications, enrollment and employment, as indicators of quality of life (QOL). MATERIALS AND METHODS: Thirty-eight children and young adults (28 men and 10 women) with iGCTs treated in our institution from 1997 to 2013 were enrolled in this study. They consisted of 26 germinomas including HCG-producing cases and 12 non-germinomatous GCTs (NGGCT). Local irradiation was selected for all patients, and the dose of irradiation was 23.4-54 Gy. The whole-brain irradiation was made in patients who had intracranial dissemination, but any prophylactic irradiation to the whole brain and spinal cord was not performed. For NGGCT, high-dose chemotherapy and peripheral blood stem cell transplantation (PBSCT) were introduced. Second-look surgeries were performed for cases with residual tumors after induction chemotherapies. RESULTS: In germinoma group and NGGCT group, 10-year progression-free survival was 86% and 84%, 10-year overall survival was 93% and 91%, respectively. About late complications, endocrinological replacement (39%), cerebrovascular disease such as cavernous hemangioma and arterial stenosis (18%), secondary neoplasm (2.6%) were observed. Regarding QOL, enrollment and return to school rate was 92% and employment and the return rate was 89%, which were influenced by hemipararesis associated with basal ganglia lesion, intractable epilepsy and whole-brain irradiation. CONCLUSION: Reduced-dose radiotherapy and intensified chemotherapy for iGCT, especially NGGCT, improved the clinical outcome and QOL of long-term survivors, suppressing late complications. Further comprehensive follow-up and analysis are needed.